Kasiturusan Sebagai Etika Solidaritas Sosial-Teologis Masyarakat Toraja - Paillin, Wiranto Bongga (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
This research aims to explore Kasiturusan culture as the Ethics of Socio-Theological Solidarity in the life of the Toraja people. Kasiturusan culture in Toraja society is essential in maintaining the unity and togetherness of the Toraja people. But in today's modern life, the culture of Kasiturusan has begun to erode and fade. This research uses the deconstruction method, data collection techniques through interviews and observations, and books and supporting articles. The results obtained are that the Kasiturusan culture is a culture that unites and strengthens the solidarity of the Toraja people through the elements contained therein. This culture is a medium that brings the Toraja people into a strong alliance. The love of Christ Jesus given to His people makes sense of solidarity well entwined in a strong and solid foundation.